A Poster Experience: From Idea to Presentation. - Will Hires (Issues in Science and Technology Librarianship)
This paper describes the creation of a poster for the poster session that was part of the ACRL Science and Technology Section program "Federal Friends: Creating Greater Access to and Support for Science and Technology Information," at the American Library Association Annual Conference in June 2010. Details about the making of the poster up to and including the final presentation serve to capture the experience and share information about the lessons learned during the process. [ABSTRACT FROM AUTHOR]